THE SACRAMENTS AS THE SPECIAL WAYS TO ENCOUNTER GOD - Luturmas, Johanis (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2021)
This study is a literatur study with a descriptive approach. The main query of this articel is: “What is the meaning of sacraments as the special ways to encounter God?Its purpose is to maintain that the sacraments are the special ways to encounter Christ because, in the sacraments, Christ is present and doing our salvation. Because of Christ’s presence in the sacrament, they confer grace. God’s grace in the sacramental celebration is abundant. Grace is a gift from God, given freely at God’s initiative unmerited and undeserved by us. But this gift does not come cheap. To have a fruitful effect on one’s life, the sacraments must be received in a good (proper) disposition and the grace of the sacraments must be put into practice. Sacraments are the special ways to encounter Christ. They are “doors to the sacred,” the Holy One.